Human Security at Zawyat Al-Hamel and its Mechanisms 1862-1920 - Bouksiba, Mohamed (Journal of Legal Studies and Researches, 2021)
In view of the colonial policy and the verses and laws that it followed, the residents of Al-Hamel region lost their spiritual, psychological, social, cultural, and economic security. In order to guarantee this human security from which the inhabitants of Si Mohamed bin Belkacem were deprived of its Zawya and through it, and thanks to our old man, the goal to which the founding sheikh was aimed was achieved.